Pendidikan Sastra Melayu di Singapura Renungan terhadap Sastera Kanak-kanak dan Remaja - Kartini Anwar (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
The power of the colonial government had brought about significant changes in Malay education system in Singapore Malay education was shaped in accordance with the needs and aspirations of the colonial, which placed its importance in the teaching of the Malay language. A bunch of texts translated fron Western literature had been used as reading materials in Malay vernacular schools. The teaching of Malay literature began to be given in Malay schools in Singapore in the 1960s. However, as these schools are closed down one by one, the teaching of Malay Iliterature will consequently be stopped. Literary works were only used in the teaching of the Malay language. In 2001, the Ministry of Education of Singapore introduced two special programs in lower and middle levels to conserve the teaching of Malay literature. These programs also serve as efforts to develop appreciation toward Malay language and culture among students. The efforts will have continuity if Elective Malay Literature is offered in high schools.This paper will discuss teaching materials in the education curriculum and the objective of the teaching of Malay literature in Singapore. Will certain selected materials in the teaching of literature bring targeted outcomes or not? The use of literary materials for children and teenagers will be discussed and several problems in selecting the materials will be diagnosed. Besides, the discourse of the literature for children and teenagers will be examined and valued in accordance with the context of present-day literature learning.The learning of Malay literature in middle level aims to give knowledge about the elements of literature and ideal values to students so that they can experience and develop respect for the Malay language, literature and social values. Through the literary materials and the teaching and learning activities, the students will be educated to think analytically, critically and creatively. Furthermore, it is expected that they can heighten their language ability and develop their sense of aesthetics if they read and analyze the Malay works of literature.